3D printing with steel: Additive Manufacturing for connections and structures. Issue 3 (17th August 2020) - Lange, Jörg; Feucht, Thilo; Erven, Maren
Abstract: Extended keynote paper of Eurosteel 2021 Automated production is finding its way into the fabrication of structural steel. One robot holds attachments (stiffeners, end plates, etc.) on a steel beam or column and another robot produces weld seams. However, welding robots can also be used for Additive Manufacturing (Wire and Arc Additive Manufacturing, WAAM). The wire electrode serves as a printing material. The Institute of Steel Construction and Materials Mechanics in Darmstadt is investigating how typical connecting elements for steel structures can be printed directly on steel beams using Additive Manufacturing with arc welding and robots. Furthermore, structural elements such as nodes for space frames can be printed and even complete structures, e.g. columns and a little bridge, have already been manufactured additively. The main focus is on determining suitable welding and process parameters. In addition, topology optimization is necessary in order to achieve good structures using a small amount of material. This is possible due to the free design prospects of WAAM, which opens up new design and production strategies.